Analysis of Groundwater Decline and Land Subsidence by using of Microgravity and Vertical Gravity Gradient Over Time Method - Suhayat Minardi; Hiden Hiden; Daharta Dahrin; Mahmud Yusuf (Jurnal ILMU DASAR, 2014)
Studies have been conducted to identify the occurrence of subsidence, a decline of groundwater, and to model the causes of subsidence in areas of Jakarta based on response of microgravity anomaly and vertical gravity gradient over time. Based on the processing and interpretation of gravity data advance of the time concluded that by using a combination of time lapse microgravity and its vertical gradient have been able to localize the source of the gravity anomaly and the results are strongly support the results of filtering to separate the source of the anomaly. The subsidence that occurs predominantly due to resettlement (in West and North Jakarta), caused by the extraction of groundwater and resettlement (in Central and East Jakarta), and dominated due to the extraction of groundwater (in South Jakarta).Keywords : Groundwater, time lapse micogravity, time lapse vertical gradient, resettlement, subsidence